Performance of two-samples pseudo-median procedure - Ahad, Nor Aishah; Othman, Abdul Rahman; Syed Yahaya, Sharipah Soaad (Faculty of Science and Technology Universiti Kebangsaan Malaysia, 2012)
This article investigates the performance of two-sample pseudo-median based procedure in testing differences between group. The procedure is a modification of the one-sample wilcoxon procedure using the pseudo-median of differences between group values as the central measure of location.The test was conducted on two groups with moderate sample sizes of symmetric distributions.The performance of the procedure was measured in terms of Type I error and power rates computed via Monte carlo methods. The performance of the procedure was compared against the t-test and Mann-Wilcoxon test.The findings from this study revealed that the pseudo-median procedure performed very well in controlling Type I error rates close to the nominal value.The pseudo-median procedure outperformed the Mann-Whitney-Wilcoxon test and is comparable to the t-test in controlling Type I error and maintaining adequate power.